ALKALINE RAINWATER PRODUCTION USING ELECTROLYSIS METHOD WITH SOLAR POWER GENERATION - Nur Prasetianto, Hafidh
Indonesia has a tropical climate with high rainfall. The high rainfall can be a potential source for further utilization, one of which is to be converted into drinking water. There is alkaline water categorized as having health benefits. The formation process of alkaline water needs to undergo a conversion process to become drinking water. The production of alkaline water can be achieved through several methods, including the pH drop method, the ionizing machine method, and the electrolysis method. The electrolysis method is chosen for its economic and effective approach in the conversion process to alkaline water. The energy demand in Indonesia is already very high, leading to an increased need for PLN electricity supply and the necessity for alternative energy sources to prevent a crisis. Solar energy can be converted into electricity using solar cells. Testing of the electrolysis system is conducted to achieve a pH level of 8.1. It takes 3.5 hours with 296 V and a current of 0.3 A for the PLN system. For the solar panel system, it takes 24 hours with 18 V and a current of 0.1 A. The ?G value for the PLN system is -3.7 kJ, and for the solar panel system, it is -8.62 kJ. Economic feasibility analysis with Net Present Value (NPV) results in $6.227,48 for the PLN electricity and $34.791,80 for the solar panel electricity. The Discounted Pay Back Period (DPBP) for PLN electricity is 2.31 years, while for the solar panel, it's 2.14 years. The Discounted Cashflow Rate of Return (DCFROR) for PLN electricity is 33.53%, and for the solar panel, it's 43.074%. Both systems are economically viable, with the solar panel system being more profitable.